Tourism research, for what? (2017)
While tourism scholars have struggled over decades to establish tourism as a valid academic discipline, it’s no less true that social scientists have developed a negative image of our colleagues. This in fact happens because for social imaginary leisure and tourism are naïve activities, or practices enrooted in an alienatory nature. Paradoxically, many of founding parents of sociology of tourism was embraced this belief, the advance of modernity, as well as tourism, will disorganize the social ties. In this essay review, we place the French Tradition under the critical lens of scrutiny revealing alternatives in tourism epistemology between tourism as a profit-oriented industry and as a mechanism of discipline.